a graphic novel - Low, Pearl; Jones, Marcia Thornton; Dadey, Debbie; reator; Dadey, Debbie (New York, NY, 2021)
"The third graders at Bailey Elementary are so hard to handle that all of their teachers have quit. But their new teacher, Mrs. Jeepers, is different -- to say the least. She's just moved from Transylvania into a spooky old house in Bailey City. She wears a mysterious brooch that glows as green as her eyes. Could Mrs. Jeepers be a vampire?"--
Keywords: Fiction; Horror stories; Fiction; Teachers; Fiction; Vampires; Fiction; Bailey School Kids (Fictitious characters); Schools; Teachers; Comic books, strips, etc; Schools; Comic books, strips, etc; Vampires; Comic books, strips, etc; Bailey School Kids (Fictitious characters); Comic books, strips, etc; Comics (Graphic works); Horror comics; Graphic novels